Self-Determined Learning, Digital Competence, and Learning Styles as Predictors of Students' Attitudes toward Flipped Learning - Muhammad Haristo Rahman; Amiruddin; Nurlaela (Sakura Digital Nusantara, 2026)
Flipped learning effectiveness depends heavily on student attitudinal acceptance, yet prior research has typically examined its determinants in isolation focusing separately on technology acceptance, self-regulation, or learning preferences. This study proposes and tests an integrated structural model linking Self-Determined Learning (SDL), Digital Competence (DC), and Learning Style (LS) to students' attitudes toward flipped learning (SFLIPP) among undergraduates in Indonesian higher education. A cross-sectional survey was administered to 395 students, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM). The measurement model demonstrated robust reliability and validity (AVE > .50; CR > .838; HTMT < .90). Results showed that Learning Style was the strongest direct predictor of attitudes (β = .413, p < .001), followed by Digital Competence (β = .190, p < .001) and Self-Determined Learning (β = .164, p < .001). SDL exerted a substantial total effect on SFLIPP (β = .535), with approximately 69.3% of this effect mediated indirectly predominantly through LS (71.4% of the mediated portion) rather than DC (28.6%). The model explained 42.7% of the variance in attitudes. These findings indicate that fostering positive attitudes toward flipped learning requires a holistic approach that simultaneously strengthens student agency, cultivates responsible digital competence, and ensures pedagogical preference alignme.